Comparison of range of motion of lower limb joints in individuals with and without overweight - Fatemeh Rezaei Tabar; Ali Asghar Norasteh (Biyumikānīk-i varzishī)
Objective: The aim of this study was to compare the range of motion of lower limb joints in overweight and obese individuals. Methods: The statistical population of the present study consisted of 25 to 45 years old working and available women in Zanjan province. These people, who included 57 people, were divided into two groups: 30 people with normal weight (mean age 31.86±6.03 years and body mass index 21.61±1.71kg / m2) and 27 people with overweight (With an average age of 35.35±6.03 years and a body mass index 27.86±1.40kg / m2). A goniometer was used to assess the range of motion of the hip, knee and ankle. After determining whether the data were normal or abnormal by Shapiro Wilk test, the normal data were analyzed through independent parametric T-test and the data which were not distributed normally were analyzed via non-parametric U Man-Whitney test. Results: The results showed that among the range of motion of the hip in both legs in flexion, extension, abduction, internal rotation and external rotation, the range of motion of the knee in both legs in flexion and the range of motion of the ankle in both legs there was a significant difference between dorsiflexion and plantar flexion movements in the two groups, but the difference between the two groups in range of motion in both legs was not significant in hip abduction and knee extension movements. Conclusion: According to the present results, it seems that being overweight can reduce the range of motion in some movements in the lower extremities. Regarding the causes researchers have proposed various factors that need further studies.